Comparative study of dynamic response by three types of energy storage systems for grid studies: A Microgrid Laboratory experimental-based study - Danny Ochoa-Correa; Edisson Villa-Ávila; Vinicio Iñiguez-Morán; Patricio Astudillo-Salinas (Revista Tecnológica)
Implementing Energy Storage Systems (ESS) is increasingly significant in power electrical systems. This is attributed to their ability to store surplus electricity generated by renewable energy sources such as wind and solar, contributing to the balance between generation and demand. Literature studies indicate that this practice enhances network stability and diminishes the need for expensive redesigns in infrastructure. This paper presents an exhaustive experimentation-based study of the dynamic response provided by three energy storage system technologies: supercapacitors, Lithium-Ion batteries, and Vanadium redox flow batteries, technologies with significant academic, research, and industrial interests nowadays. The objective of this research is the experimental evaluation of the performance of such technologies in real electrical system operations, focusing on determining the efficiency of charge and discharge, as well as the tracking of active and reactive power achieved through the associated grid interface. The experimental tests performed in a microgrid laboratory show these technologies’ advantages and limitations in different grid-integration applications, with the Lithium-Ion battery-based ESS demonstrating the highest efficiency and faster power response. The results achieved and reported in the article can serve as an essential input for researchers and technology developers to feed their models with more precise parameters and data that might provide results closer to the actual behaviour of the studied prototypes. The methodological framework used in this research is descriptive, experimental, and quantitative.